(untitled) (Journal of Libya for geographical studies, 2026)
The objective this study is to analyze the spatio-temporal variability of precipitation amounts, in order to provide an objective assessment of its impacts on water resources. The analysis of precipitation variability was carried out in the M’dez watershed, which is distinguished by a diverse morphological mosaic. The rainfall parameters analyzed, for the period 1970-2024, include monthly, seasonal and annual average. Meteorological data were obtained from rainfall stations managed by the Sebou Basin Hydraulic Agency. In addition, precipitation anomalies were calculated and the standardized precipitation index (SPI) was calculated. For the study area, there was a high variability in precipitation amounts, both in terms of recorded values and the inconsistency of the years in which they occurred.